2011
DOI: 10.1111/j.1365-2850.2011.01706.x
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization of schizophrenia as perceived by nurses, medical doctors, medical students and patients

Abstract: Stigmatization of schizophrenia is widespread and its genetic explanation may potentially increase the stigma. The present study investigated whether seeing schizophrenia as a genetic or environmental disorder might influence perceived beliefs towards people with schizophrenia and whether social stigmatizing attitudes were differently perceived the 202 subjects who were recruited. Perceived social stigmatizing attitudes were compared among participants who read two vignettes depicting a person with schizophren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 43 publications
(50 reference statements)
3
62
0
Order By: Relevance
“…Twelve studies were determined to be of high quality (Arvaniti et al, 2009; Chambers et al, 2010; Foster et al, 2008; Hamdan-Mansour & Wardam, 2009; Hsiao et al, 2015; Linden & Kavanagh, 2012; Magliano et al, 2004; Munro & Baker, 2007; Nordt, 2006; Scheerder et al, 2011; Serafini et al, 2011; Sevigny et al, 1999). One study score within the moderate quality range (Kukulu & Ergun, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies were determined to be of high quality (Arvaniti et al, 2009; Chambers et al, 2010; Foster et al, 2008; Hamdan-Mansour & Wardam, 2009; Hsiao et al, 2015; Linden & Kavanagh, 2012; Magliano et al, 2004; Munro & Baker, 2007; Nordt, 2006; Scheerder et al, 2011; Serafini et al, 2011; Sevigny et al, 1999). One study score within the moderate quality range (Kukulu & Ergun, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported positive attitudes (Chambers et al, 2010; Linden & Kavanagh, 2012; Munro & Baker, 2007) and four studies exemplified negative attitudes (Hamdan-Mansour & Wardam, 2009; Hsiao et al, 2015; Magliano et al, 2004; Sevigny et al, 1999). The remaining studies were a combination of both positive and negative (Foster et al, 2008; Kukulu & Ergun, 2007; Nordt et al, 2006; Serafini et al, 2011). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the most negative scores were found in reports of opinions about paranoid schizophrenia. Similar to findings obtained from the general population, research has shown that medical students are prejudiced towards people with mental disorders, as they state that such patients have a hard time recovering and that difficult psychiatric patients are violent and dangerous (9)(10)(11). Pharmacy students have also stated that patients with schizophrenia are unstable and dangerous (12).…”
Section: Introductionmentioning
confidence: 66%
“…However, it should be mentioned that in studies that compared the stigmatization of schizophrenic patients among medical nurses, physicians, medical students and patients, the Table 3. Mean values of the summed score on the Likert scale in relation to age and previous high school education highest level of stigmatization was found in medical students (11). Most research has shown that education against stigma is efficient (26,27).…”
Section: Discussionmentioning
confidence: 98%